SYOFIANI BUSTAMAM SEBAGAI PENDIDIK DAN SENIMAN TARI MINANG TAHUN 1965-2013 - Gunawan, Hari Arifki; Nurhuda, Ahmad; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
This skripsi is a study Thematic Biography by choosing Syofiani Bustamam as the object of the research study. Syofiani Bustamam a dance educator and artist Minang years 1965-2013. This study aims to explain how Syofiani Bustamam role as an educator and artist Minang dance. research methods used in this research is the history of the stage heuristic method, source criticism, Interpretation and Historiography. Syofiani Bustamam became a lecturer in 1965-2013, it is not independent of achievement as an artist Syofiani Minang dance. as a lecturer Syofiani Bustamam have strong character and conscientious but remained friendly to the students. Bustamam Syofiani as an artist has also created 20 Minang dance and also have gained many-awards both national and Internasionl.